Clownfish - Durant, Alan (London Walker Books Ltd, 2018)
From award-winning author Alan Durant comes a surreal, poignant story about family bonds and loss. Dak's dad has been dead for seven days when suddenly he reappears. He's the same in almost every way, with one startling exception: Dad has turned into a clownfish, and now lives in a tank at their local aquarium. Dak is delighted by the news - he has Dad back, even if he isn't quite as he was before. Deciding to keep Dad's transformation a secret, Dak visits him at the aquarium as often as he can, and ends up spending so much time there that they offer him a job. This is how he comes to meet Violet, the owner's prickly but kindhearted niece; when the aquarium is threatened with closure, the pair must work together to save it. For Dak, the stakes couldn't be higher ... after all, if the aquarium shuts down, what will happen to the fish? In parts wry, moving and undoubtedly strange, this beautifully crafted story will stay with you long after the final page.